INTEGRATIVE CURRICULUM MANAGEMENT IN IMPROVING THE QUALITY OF FORMAL EDUCATION AT DAARUSY SYIFA AL ISLAMI ISLAMIC BOARDING SCHOOL KUDUS ACADEMIC YEAR 2025/2026 - Iva Badiatuz Zahro; Subaidi Subaidi; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the management of the integrative curriculum in an effort to improve the quality of formal education at Daarusy Syifa Al Islami Islamic Boarding School (Pondok Pesantren) Kudus in the 2025/2026 academic year. The research focus includes the core aspects of management: planning, organizing, implementing, and evaluating a curriculum that seamlessly combines national education standards with the distinct religious values of an Islamic boarding school. This study employs a qualitative approach with a case study design. Data were collected through field observations, in-depth interviews with the school leadership, educators, and students, as well as an extensive study of curriculum documentation. The results indicate that the integrative curriculum management at Daarusy Syifa Al Islami Islamic Boarding School has been implemented systematically through the synchronization of the academic calendar, professional collaboration among general and religious educators, and the thematic integration of scientific subjects with Islamic religious values. Periodic and participatory evaluations have proven effective in maintaining educational quality and enhancing students’ competitiveness in both academic and non-academic fields. The conclusion of this study confirms that an integrative curriculum managed with professional management can be a viable solution in balancing intellectual mastery and spiritual maturity, thereby producing graduates who are competitive, possess strong character, and remain committed to Islamic traditions